PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENJUALAN MIE BERFORMALIN DI KOTA PEKANBARU - Nova Putri; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Law enforcement is a series of efforts, processes and activities to make the law work properly. One of the problems that still occur today is the criminal problem of selling formalized noodles in the Pekanbaru area. The problem of the criminal act of selling formaldehyde noodles is a very important legal problem because it can give an indication to public health, the authors still see many yellow (wet) noodle sellers who have not fulfilled proper food sales procedures maximally. so that researchers need to research related to how law enforcement related to the criminal act of selling formalin noodles in the Pekanbaru area. The purpose of writing this thesis is First to find out the law enforcement related to the criminal act of selling formalized noodles in Pekanbaru. Second, to find out obstacles in the law enforcement process related to the criminal act of selling formalized noodles in Pekanbaru. Third, to find out the ideal law enforcement solution to prevent criminal acts of selling formalized noodles in Pekanbaru.This type of research is sociological legal research, namely research that seeks a correlation between law and society. This research is descriptive in nature, namely the researcher tries to provide an overview of the cases being studied. In this study using qualitative data analysis, which means explaining and concluding about the data that has been collected by the author. This study uses codified primary and secondary data.The results of this study are law enforcement against yellow (wet) noodle sellers who are known to have problems in terms of food or the production process is not optimal. When a criminal sanction has been given, whether in the form of a warning letter of the danger of imprisonment or something else, the same case still occurs so that the prevention of this case must be carried out maximally through more stringent means or procedures. The obstacles in law enforcement are focused on one object, namely